2020
DOI: 10.3390/cells9040808
|View full text |Cite
|
Sign up to set email alerts
|

NeuroHeal Treatment Alleviates Neuropathic Pain and Enhances Sensory Axon Regeneration

Abstract: Peripheral nerve injury (PNI) leads to the loss of motor, sensory, and autonomic functions, and often triggers neuropathic pain. During the last years, many efforts have focused on finding new therapies to increase axonal regeneration or to alleviate painful conditions. Still only a few of them have targeted both phenomena. Incipient or aberrant sensory axon regeneration is related to abnormal unpleasant sensations, such as hyperalgesia or allodynia. We recently have discovered NeuroHeal, a combination of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Probably, the controversy of whether to boost autophagy is not the issue to tackle, but its fine-tune activation may yield protective effects. Indeed, we have recently reported that NeuroHeal-fine-tuned autophagy promotes neuroprotection of neonatal motoneurons, improves motor axonal regeneration, and has a role in neuropathic pain [20,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the controversy of whether to boost autophagy is not the issue to tackle, but its fine-tune activation may yield protective effects. Indeed, we have recently reported that NeuroHeal-fine-tuned autophagy promotes neuroprotection of neonatal motoneurons, improves motor axonal regeneration, and has a role in neuropathic pain [20,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides are key regulators of peripheral nociception and contribute to the mechanisms regulating central sensitisation to pain. In many cases, chronic inflammation, ion channel imbalance and a lack of inhibition in the dorsal horn of the spinal cord partake in maintaining pain sensation [182]. PACAP and VIP are expressed across key anatomical regions/structures that are important in somatosensory processing and the transmission of pain signals [183].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…The overlap between pain and inflammatory signalling has been extensively studied and reviewed [189]. Addition-ally, an association between axonal regeneration and pain has been hypothesised, with evidence suggesting that accelerated regeneration may ameliorate pain of nerve origin [182]. PACAP and VIP have well-described roles in promoting axonal regeneration after peripheral nerve injury [34,191].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Drug repurposing for other indications facilitates its readiness for clinical use, since their PD and PK are well-known in humans. We have previously reported its neuroprotective effects in different neurodegenerative models [ 12 , 14 , 15 , 16 ]. In addition, we recently observed that NeuroHeal protects the muscle by reducing atrophy induced by denervation or by immobilization [ 17 ], suggesting it may have also protective effects in other types of myopathies.…”
Section: Introductionmentioning
confidence: 99%